Microenterprise Cash Management Training for Mitigating Financial Distress - Ikhtiari, Kirana; Nurfadila, Nurfadila; Muslim, Muslim; Sutisna, Entis; Ameliana, Yana (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study aims to examine the impact of cash management training on mitigating financial distress among microenterprises, particularly in developing economies. It explores how internal capabilities and external factors influence the effectiveness of cash management practices and contribute to the financial resilience and sustainability of microenterprises. Research Design and Methodology: A systematic literature review (SLR) was conducted, analyzing recent academic articles, peer-reviewed journals, and scholarly publications on cash management, financial distress, and microenterprise sustainability. The research synthesized findings across various contexts to provide a comprehensive understanding of the topic. Findings and Discussion: The study found that cash management training significantly enhances the financial resilience of microenterprises by equipping owners with essential skills for managing cash flows. The effectiveness of these practices is influenced by external factors such as supportive government policies and access to financial services. The research highlights the importance of adaptability in cash management, particularly in volatile economic conditions, and underscores the role of both internal and external factors in sustaining microenterprises. Implications: The findings suggest that policymakers and financial institutions should focus on creating an enabling environment that supports microenterprises through targeted training and financial inclusion initiatives. The study also provides practical insights for microenterprise owners to continuously adapt their cash management strategies, ensuring long-term business sustainability.